1996
DOI: 10.1152/ajpgi.1996.270.5.g757
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandins in intestinal epithelial restitution stimulated by growth factors

Abstract: Mucosal integrity is reestablished after superficial injuries by a rapid resealing process, termed epithelial restitution, that is regulated by several growth factors and cytokines. Growth factors are also known to stimulate the synthesis of endogenous prostaglandins that mediate important functions in intestinal epithelial cells. Therefore, we examined the effect of endogenous eicosanoid production modulators, piroxicam, dexamethasone, and nordihydroguaiaretic acid (NDGA) on intestinal epithelial restitution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 0 publications
1
29
2
Order By: Relevance
“…[29][30][31][32] EGF also regulates cell motility, proliferation, and maintenance of cell size and shape. [34][35][36][37][38][39][40][41][42][43] Our data show that probiotic pretreatment is able to preserve EGFr function that would otherwise be affected adversely by EIEC invasion. This observation likely implies an important mechanism whereby probiotics could improve mucosal function in a wide variety of intestinal disorders, given the protean functions of EGF and related growth factors in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 87%
“…[29][30][31][32] EGF also regulates cell motility, proliferation, and maintenance of cell size and shape. [34][35][36][37][38][39][40][41][42][43] Our data show that probiotic pretreatment is able to preserve EGFr function that would otherwise be affected adversely by EIEC invasion. This observation likely implies an important mechanism whereby probiotics could improve mucosal function in a wide variety of intestinal disorders, given the protean functions of EGF and related growth factors in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 87%
“…Alternatively, the observed effects of COX-2 inhibitors on colonic wound healing may have been due to local tissue factors (skin wounds having a more abundant blood supply). However, differential sensitivities of cellular healing responses to cytokines between the gut and skin have been suggested previously 34 , with disproportionately high levels of prostaglandin activity 35 and collagen deposition 36 noted in colonic anastomoses. Further studies are required to resolve this issue.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the present findings suggest that prostaglandins play a salutary role in early restoration of epithelial barrier function. Although repair mechanisms attributed to prostaglandins have previously included enhanced epithelial restitution (6), and subepithelial myofibroblast contraction (7), increased resistance of tight junctions appears to provide an equally important method of rescuing barrier function. The mechanism by which prostaglandins regulate paracellular permeability is unknown, but may include alteration of tight junction structure or functional regulation via second messengers.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the cytoprotective effects of prostaglandins are actually due to enhanced tissue repair, rather than prevention of injury (4). Recent studies have shown that stimulation of epithelial migration (restitution) by growth factors is mediated by prostaglandins, since inhibition of cyclooxygenase prevented growth factor-stimulated restitution, and replacement of prostaglandins restored the migratory process (6). In addition, prostaglandins have been shown to stimulate villous contraction in the small intestine (7), which aids restitution by decreasing villous surface area (8).…”
Section: Introductionmentioning
confidence: 99%